2016
DOI: 10.1016/j.devcel.2016.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Cell Competition and Its Role in the Regulation of Cell Fitness from Development to Cancer

Abstract: Cell competition is a cell fitness-sensing mechanism conserved from insects to mammals that eliminates those cells that, although viable, are less fit than their neighbors. An important implication of cell competition is that cellular fitness is not only a cell-intrinsic property but is also determined relative to the fitness of neighboring cells: a cell that is of suboptimal fitness in one context may be "super-fit" in the context of a different cell population. Here we discuss the mechanisms by which cell co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
102
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(104 citation statements)
references
References 98 publications
1
102
1
Order By: Relevance
“…Cell competition is a contact-dependent cellcell interaction mechanism that eliminates slowly dividing cells or damaged cells with tumorigenesis potential, a mechanism that can sometimes be hijacked by tumor cells to expand at the expense of wild-type (WT) neighbors (43,44) (Fig. 5A).…”
Section: Manipulation Of Neighboring Cells To Study Cell-cell Competimentioning
confidence: 99%
“…Cell competition is a contact-dependent cellcell interaction mechanism that eliminates slowly dividing cells or damaged cells with tumorigenesis potential, a mechanism that can sometimes be hijacked by tumor cells to expand at the expense of wild-type (WT) neighbors (43,44) (Fig. 5A).…”
Section: Manipulation Of Neighboring Cells To Study Cell-cell Competimentioning
confidence: 99%
“…This is also a key trait of cancer, where clonal growth is promoted as a response to active selection [72,73]. MYC activation is considered a hallmark of cancer initiation and maintenance [74], and the discovery of MYC function in CC has primed a series of speculations about a possible role for this phenomenon in cancer [71,75,76,77,78]. Tumours undergo continuous genetic diversification and epigenetic plasticity followed by clonal selection and expansion, revealing a genetic architecture reminiscent of Darwin’s evolutionary trees [79].…”
Section: Myc Cell Competition and Cancermentioning
confidence: 99%
“…by generating an age-associated, neoplastic-prone tissue landscape [3]. Similarly, Henry et al have reported that aging-associated inflammation promotes selection for adaptive oncogenic events in B cell progenitors [2]; it was proposed that cell competition may in fact drive the emergence of oncogenically altered cells in a background of age-induced decline in tissue fitness, in a process that has been referred to as “adaptive oncogenesis” [4, 6]. …”
Section: Introductionmentioning
confidence: 99%